Planteamiento y evaluación de las soluciones ejecutadas por la concesionaria, en las intervenciones de puesta a punto del km 544+870 al km 588+183 del tramo II de la carretera iirsa Norte - Macedo Huamán, Yasser Franklin (2015)
This thesis was developed at the Professional School of Civil Engineering, Faculty of Civil Engineering and Architecture at the National University of San Martin-Tarapoto purposes degree in Civil Engineering, with the working point interventions tuning km. 544 + 870 to km. 588 + 183 section 11 (Tarapoto Rioja) of the IIRSA Norte highway. The purpose of this paper is to present the results of the current assessment of the pavement of this road in the said section, that his chance had been operated by the Concessionaire by solutions whose methodology is explained and detailed. By the resulting information was learned the technical resources which served as elements of solution to problems in road maintenance. So actively it participated in the production of new knowledge with positive points for the community and science. · It was featured data collection and information Maintenance Technical Report used by the Concessionaire for initial planning and execution of the work; the second part was done by taking data directly from the field, using the methodology for initial evaluations according to the components Concession contract documents, that the contractor uses. Then, based on initial assessments, physical interventions and current assessment, we have been interpreted and discussed the results to determine the performance and effectiveness of the solutions implemented and propose, where it has not been positive interverción, new studies and breadth interventions, as established under the Concession, understanding that gathers sufficient technical criteria and guidelines for track maintenance. As achievements we have to implement this work, it has allowed the approach of interventions, implementing them and the final evaluation of the executed, which has been gaining experience in the process, meeting the criteria for the current assessment. Validation supported by statistical parameters such as the "t" Student hypothesis indicates that the solutions implemented by the Concessionaire has an effect on interventions tuning km. 544 + 870 to km. 588 + 183 Section 11 of the road under study. Therefore, aware of our social responsibility as an integral part of the National University of San Martin we are contributing to participate in road problems, as well as economic and social development of the community and therefore of our country by providing a reference document for cases of similar situations in engineering maintenance of asphalt roads of the jungle.